Optimizing the Opening Structure of Public Speaking in Da'wah Opening - Hakiki, Ridwan Daril; Suryandari, Meity (Peneliti.net, 2023)
This material discusses the understanding that public speaking in the Islamic context has a rich historical heritage, practiced by the prophets, especially the Prophet Muhammad. As the art of public speaking, public speaking is not only about conveying information but also building connections, inspiring, and bringing about change. The focus of this research is the opening structure as a key element in Islamic public speaking, with an emphasis on topic selection, effective introduction, and public speaking competence. Through content analysis and literature references, this research reveals that public speaking plays an important role in Islamic da'wah, where choosing the target of da'wah becomes an important strategy. Public speaking competence, such as choosing useful topics and interesting introductions, has proven to be a key element in the effectiveness of da'wah. This research provides practical and in-depth solutions, highlighting changes that can be made, such as catchy titles and the use of more descriptive language, to increase the positive influence in spreading Islamic teachings. Mastery of public speaking competence in and understanding of good opening structures has the potential to increase the effectiveness of Islamic da'wah, providing communication between the speaker and the audience.